2007
DOI: 10.1017/s0025315407054215
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenose dolphin (Tursiops truncatus) presence and incidental capture in a marine fish farm on the north-eastern coast of Sardinia (Italy)

Abstract: On the north-eastern coast of Sardinia, from November 2004 to January 2006, the first attempt in the Mediterranean basin to obtain information on encounter rate, group size and incidental capture of bottlenose dolphins in a marine fish farm was assessed, combining direct observations from fish farm boats with photo-identification studies. During 15 months of research, 79 d (65.3% of the total monitored days) were spent in direct observation of 146 groups of bottlenose dolphins around the fish farm cages. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 9 publications
(13 reference statements)
0
43
0
3
Order By: Relevance
“…Bacher et al, 2012), as well as some marine mammals whose populations are deemed "critically endangered" in the Mediterranean, such as Bottlenose Dolphin (Tursiops truncatus) (criterion A3bcd; C1), and Monk Seal (Monachus monachus) (criterion A2abc; C2a(i); E) (e.g. Güç lüsoy and Savas, 2003;Díaz-López and Bernal-Shirai, 2007;Piroddi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bacher et al, 2012), as well as some marine mammals whose populations are deemed "critically endangered" in the Mediterranean, such as Bottlenose Dolphin (Tursiops truncatus) (criterion A3bcd; C1), and Monk Seal (Monachus monachus) (criterion A2abc; C2a(i); E) (e.g. Güç lüsoy and Savas, 2003;Díaz-López and Bernal-Shirai, 2007;Piroddi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, human activities influence the distribution of food resources and dolphins behaviour (Díaz López, 2006a,b;Díaz López, 2009), which promote the evolution of social organizations (Díaz López and Shirai, 2008) and individual preferences for the area (Díaz López and Shirai, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Two fish farms operated a total of 30 floating cages in Serra Gelada during the study period. Open cage aquaculture in the Mediterranean Sea has been shown to benefit bottlenose dolphins by making it easier for them to catch prey near the cages (Díaz L opez and Bernal Shirai, 2007;Piroddi et al, 2011), therefore, we expected to find a high % DPH in Serra Gelada due to the attraction effect of fish farming operations. Furthermore, Raga & Pantoja (2004) suggested that a resident population of bottlenose dolphins might be present in this region based on the spatial and temporal distribution of sightings obtained in their study.…”
Section: Overall Bottlenose Dolphin Presencementioning
confidence: 97%